2013
DOI: 10.2298/sarh1302041s
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between obesity, lipids and fasting glucose in the menopause

Abstract: Gaining weight and decreased SHBG are related to dyslipidemia and increased fasting glucose confirming increased incidence of metabolic abnormalities in the menopause.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Netjasov et al . [ 28 ] found that BMI and glucose level were significantly and positively correlated among the obese and overweight females with a BMI ≥25.0 kg/m 2 . Khoo et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Netjasov et al . [ 28 ] found that BMI and glucose level were significantly and positively correlated among the obese and overweight females with a BMI ≥25.0 kg/m 2 . Khoo et al .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Netjasov et al . [ 28 ] reported the identification of significant negative correlations between BMI and HDL in obese and overweight females with a BMI ≥25.0 kg/m 2 . Gaining weight was associated with dyslipidemia in another study, confirming the increased incidence of metabolic abnormalities during menopause.…”
Section: Discussionmentioning
confidence: 99%